Effective location of active control devices for building vibrations caused by periodic excitation acting on intermediate storey. - Xing, Liping (Earthquake engineering & structural dynamics.)
In order to investigate ways of reducing vibrations of building structures subjected to excitation acting on intermediate storey, active vibration controls are conducted with active control devices installed on different floors of the structure and the effective location of control devices is also investigated. In this paper, we propose a new 'Discrete Optimizing Control Method' for vibration control. The control forces are determined analytically which makes the 'discrete index function' minimum. Through numerical simulation, the Discrete Optimizing Control Method is proved to be an effective control method. The response reduction effects are the best when the control devices are concentrated on the adjacent three floors of the vibration source.